Cluster randomized trial of a multifaceted primary care decision-support intervention for inherited breast cancer risk. - Wilson, B; Torrance, N; Mollison, J; Watson, MS; Douglas, A; Miedzybrodzka, Z; Gordon, R; Wordsworth, S; Campbell, M; Haites, N; Grant, A (2006)
BACKGROUND: GPs are increasingly expected to meet the needs of patients concerned about their risk of inherited breast cancer, but may lack skills or confidence to use complex management guidelines. We developed an evidence-based, multifaceted intervention intended to promote confidence and skills in this area. OBJECTIVE: To evaluate the effectiveness of the intervention in improving GP confidence in managing patients concerned about genetic risk of breast cancer. METHODS: DESIGN: Cluster randomized controlled trial. SETTING: General practices in the Grampian region of Scotland. SUBJECTS: GPs and the patients they referred for genetic counselling for risk of breast cancer. MAIN OUTCOME MEASURES: GPs' self-reported confidence in four activities related to genetics; rates of referral of patients at elevated genetic risk; and referred patients' understanding of cancer risk factors. RESULTS: No statistically significant differences were observed between intervention and control arms in the primary or secondary outcomes. A possible effect of the intervention on the proportion of referred patients who were at elevated risk could not be discounted. Only a small proportion of intervention GPs attended the educational session, were aware or the software, or made use of it in practice. CONCLUSIONS: No convincing evidence of the effectiveness of the intervention was found, probably reflecting barriers to its use in routine practice.